Case study of the London 2012 Olympic and Paralympic pharmacy service preparations. (13th October 2014) - File, Hayley; Thomas, Trudy; Anderson, Geoff
Abstract Objectives The Pharmacy Clinical Services Group (PCSG) was formed in 2009. Its aim was to design and deliver a world‐class pharmacy service to 250 000 accredited persons and consider the pharmaceutical needs of 9.2 million visitors to the London 2012 Games. Methods The explanatory case study method was used to investigate how the PCSG prepared and how they considered the wider vision of the Games. The study investigated two propositions: (1) that the PCSG has a communication function and (2) that it has a design function. A range of data were examined using NVivo 9 data management software. Key findings The study identified four emerging themes and a number of subthemes. Conclusions The study validated the propositions and highlighted that the PCSG had a leading role within the wider multidisciplinary team. The study found that the PCSG embraced the wider vision of the Games and was exceptionally well prepared to deliver a world‐class pharmacy service, anticipating a new gold standard for the provision of pharmacy services for future sporting events.